2023
DOI: 10.1200/go.23.00002
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Oncology Research in Asia: Current Status and a Peep Into the Future From the Federation of Asian Organizations for Radiation Oncology

Abstract: PURPOSE This survey was conducted to assess the current research practices among the 14 members of the Federation of Asian Organizations for Radiation Oncology (FARO) committee, to inform measures for research capacity building in these nations. MATERIALS AND METHODS A 19-item electronic survey was sent to two research committee members from the 14 representative national radiation oncology organizations (N = 28) that are a part of FARO. RESULTS Thirteen of the 14 member organizations (93%) and 20 of 28 member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…28 Similar themes have been observed among ROs in neighboring countries as well. A study by Chopra et al 29 examined the research landscape in Federation of Asian Radiation Oncologists member organizations including PROS and found that only 5%-20% of ROs were actively publishing, and 75%-80% of research conducted were retrospective and observational studies. Commonly cited barriers were time, funding, and research training and mentorship, as expected in a region of mostly LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…28 Similar themes have been observed among ROs in neighboring countries as well. A study by Chopra et al 29 examined the research landscape in Federation of Asian Radiation Oncologists member organizations including PROS and found that only 5%-20% of ROs were actively publishing, and 75%-80% of research conducted were retrospective and observational studies. Commonly cited barriers were time, funding, and research training and mentorship, as expected in a region of mostly LMICs.…”
Section: Discussionmentioning
confidence: 99%